Effect of desensitizing toothpastes on dentin - Shelon Cristina Souza Pinto; Camila Maggi Maia Silveira; Márcia Thaís Pochapski; Gibson Luiz Pilatt; Fábio André Santos (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The objective of this study was to analyze the effects of toothbrushing with desensitizing toothpastes on dentin permeability and dentinal tubule occlusion. Fifty rats provided two hundred incisor teeth divided into five groups: DW, brushed with distilled water (control); FT, brushed with fluoride toothpaste; SCT, brushed with strontium chloride toothpaste; PCT, brushed with potassium citrate toothpaste; and PNT, brushed with potassium nitrate toothpaste. Cavities were prepared to expose the dentinal tubules, and the incisor teeth were brushed using the experimental agents. After each treatment, Evans blue dye solution was applied to the teeth. Dentin permeability was analyzed using scanning electron microscopy and energy-dispersive X-rays (EDX). There were significant differences (p < 0.0001, ANOVA) among the groups regarding dentin permeability, number of dentinal tubules, diameter of dentinal tubules, and opened tubular area. In the SCT, PCT and PNT groups, opened and partially occluded tubules, deposits, and a few smear layers were observed. In the DW and FT groups, most of the dentinal tubules were open, with no deposits or smear layers on the dentin. EDX revealed peaks of calcium and phosphorus in all of the groups, as well as traces of strontium in the SCT group and of potassium in the PCT and PNT groups. Desensitizing toothpaste decreased dentin permeability, although it produced only partial dentin tubule occlusion.